Pengaruh pertumbuhan ekonomi, pendapatan asli daerah dan dana alokasi umum terhadap anggaran belanja modal di Provinsi Jambi Tahun 2001-2023 - Damayanti, Fachnilu; Hari Prihanto, Purwaka; Artis, Dearmi (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2024)
This study aims to: 1) Analyse the development of Economic Growth, Regional Original Revenue and General Allocation Fund on Capital Expenditure in Jambi Province during 2001-2023. 2) Analyse the effect of Economic Growth, Regional Original Revenue and General Allocation Fund on Capital Expenditure in Jambi Province during 2001-2023. Data is sourced from the Jambi Province Central Statistics Agency (BPS). The data was analysed using multiple linear regression models. The results showed that simultaneously Economic Growth, Regional Original Revenue and General Allocation Fund had a significant effect on Capital Expenditure. Meanwhile, partially Local Original Revenue and General Allocation Fund have a significant effect on Capital Expenditure in Jambi Province.